2012
DOI: 10.1007/s00296-012-2561-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclophosphamide on cytokines in patients with primary Sjögren’s syndrome-associated interstitial lung disease in South China

Abstract: The objective of the study is to investigate the mechanisms of cyclophosphamide sequential therapy for patient with primary Sjögren's syndrome-associated interstitial lung disease (PSS-ILD). This was a retrospective review of 15 patients (2005-2008) with PSS-ILD who underwent cyclophosphamide sequential therapy. Peripheral blood and bronchoalveolar lavage (BALF) were obtained before and 3, 6, 12 and 24 months after the treatment. The TNF-α and TGF-β1 mRNA levels in peripheral blood were measured using reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…In terms of treatment, this study showed that cyclophosphamide (CTX) can help to improve the progression of pSS‐ILD patients. A previous study 20 showed that the use of CTX in pSS‐ILD patients may inhibit tumor necrosis factor‐α, and then inhibit transforming growth factor‐β1 and matrix metalloproteinase‐9, and finally inhibit the progression of pulmonary fibrosis, which elucidated the effectiveness of CTX from the perspective of mechanism. Although CTX was not associated with survival in prognosis analysis, it was suggested that CTX can be considered as one of the effective drugs in the treatment of ILD in patients with pSS‐ILD.…”
Section: Discussionmentioning
confidence: 97%
“…In terms of treatment, this study showed that cyclophosphamide (CTX) can help to improve the progression of pSS‐ILD patients. A previous study 20 showed that the use of CTX in pSS‐ILD patients may inhibit tumor necrosis factor‐α, and then inhibit transforming growth factor‐β1 and matrix metalloproteinase‐9, and finally inhibit the progression of pulmonary fibrosis, which elucidated the effectiveness of CTX from the perspective of mechanism. Although CTX was not associated with survival in prognosis analysis, it was suggested that CTX can be considered as one of the effective drugs in the treatment of ILD in patients with pSS‐ILD.…”
Section: Discussionmentioning
confidence: 97%
“…In patients with diffuse lung parenchymal disease, T lymphocytes may express TGF-β in the lung tissue; TGF-β is an effective anti-inflammatory regulator and profibrotic cytokine [ 36 ]. Our previous study found that the serum level of TGF-β1, a key factor in the development of diffuse alveolar injury, alveolar endothelial cell necrosis and pulmonary fibrosis [ 37 , 38 ], was much higher in patients with ILD than in patients without ILD [ 32 ]. Thus, TGF-β-expressing T cells, particularly Th2 and Treg cells, may also be involved in the development of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with active pSS, rituximab, belimumab and abatacept have also been used, but this treatment is uncommon due to its high cost, and questions relating to its usefulness in pSS still remain unanswered. [21][22][23][24] In conclusion, pulmonary involvement in pSS is common and occurs in around 30% of patients. This represents one of the most intriguing aspects of the disease.…”
Section: Discussionmentioning
confidence: 99%